The role of creativity in Project Management success - Padayachee, Vanashree (University of the Witwatersrand, Johannesburg, 2021)
Creativity has always been valued throughout the centuries. This study investigates the role of creativity in project management success. Primary data collection was conducted through an online survey. Analysis was done through the Pearson‘s Correlation and One Way Annova. The results show that the output of the regression analysis indicates that Creativity is significant with a p<0.000 and positive coefficient of 0.920 with standard error of 0.070 suggesting that Creativity has a stronger positive impact on Project Success. The findings should benefit project management specialists by highlighting the importance of creativity in teams in achieving project management success
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: Creativity; Project Management Success; UCTD; UCTD; SDG-8: Decent work and economic growth